Vespula vulgaris ... - Dvořák, Libor; Castro, Leopoldo (Zenodo, 2007)
Vespula vulgaris (Linnaeus, 1758) Material examined. SPAIN: CIUDAD REAL PROVINCE, Cortijo de Arriba, 39º18′ N, 04º03′ W, forest with Quercus rotundifolia and undergrowth of Daphne gnidium , Thymus sp. and Phillyrea angustifolia , 850 m a.s.l., 12.vii.- 16.viii.2006, 1 ♀, beer-baited trap, E. Jordán leg., L. Dvořák det. & coll. Widespread species known from all of Europe, across the Palaearctic part of Asia to Japan and most of North America, from Alaska to northern Mexico; introduced to Iceland, New Zealand, Australia (Victoria, Tasmania) and Hawaii (CARPENTER & KOJIMA 1997). In Spain this species has a contiguous distribution only in the northern half, whereas in the rest of the country it is restricted to the highest parts (MADERO MONTERO 1988). First record from Ciudad Real province. ... : Published as part of Dvořák, Libor & Castro, Leopoldo, 2007, New and noteworthy records of vespid wasps (Hymenoptera: Vespidae) from the Palaearctic region, pp. 229-236 in Acta Entomologica Musei Nationalis Pragae 47 on page 234, DOI: 10.5281/zenodo.5328343 ...